A Semantic Approach to Architectural Ornamentation in Monuments of Persian Garden - Ali Bamdad (Journal of Architecture, Planning and Construction Management, 2020)
No one can deny Persian garden as a symbol of Iranian architecture in the course of time. Since the long time, Persian Garden has Constant physical characteristics that could preserve Iranian identity, more than any other Persian artistic phenomena. On the other hand, it could adapt itself with each specific part of Religious mystery. As the essence of Persian artist try to get every phenomenon mysterious and scared side to build, The Persian garden is not an exception and behind its tempting and imaginary fairness hide a sacred part. Scrutiny of Persian garden’s frame work, a unique Persian Pleasant, indicates that it has been always a guest of every Iranian people, which lead us to analyze Investigation about this mysterious and sacred face. The research would revolve around homogeny of the Spiritual Principles of Persian Garden in the point of 4 approaches such as: Quran paradise, Iranian cosmos, Persian Sufism and Iranian identity. After that, this research proposes to group the values of Persian garden based on Donald Wilber’s idea on a new concept. Then, by selecting the monuments of Persian garden in a comparative study with mosques decorations, we try to unravel the mysteries of architectural ornamentations in Persian garden. We hope our endeavor stimulate your encouragement.